AC losses of Rutherford MgB2 cables made by powder-in-tube and internal magnesium diffusion processes. (5th November 2018) - Kováč, J; Kulich, M; Kopera, L; Kováč, P
Abstract: Magnetization losses of Rutherford MgB2 cables of different sheath materials (Cu, CuNi and Al + Al2 O3 ) made by powder-in-tube and internal magnesium diffusion processes were studied experimentally. Short cable samples consisting of 12 strands were measured in the temperature range from 18 K up to 40 K, external fields up to 70 mT and frequencies 72 Hz and 144 Hz. The effects of inter-strand resistance by soldering and external field orientation (perpendicular and parallel) were also tested. The impact of eddy current losses in the sheath material was determined by the loss measurement in cable samples without MgB2 . It was found that very high eddy current losses of Cu sheathed strands overlap the hysteresis loss. The lowest AC losses at 20 K were measured for a Rutherford MgB2 cable with an Al + Al2 O3 sheath, which makes it attractive for applications where low loss and also low coil mass are required (e.g. wind turbines or airborne engines).